Click, Clack, Surprise! - Cronin, Doreen; Lewin, Betsy (New York : Atheneum Books for Young Readers, 2016)
Little Duck celebrates his first birthday with the other animals on the farm by copying their examples, from shearing off all his feathers to taking a mudbath, before enjoying Farmer Brown's yummy frosted maple cake.
Keywords: Ducks -- Juvenile fiction; Domestic animals -- Juvenile fiction; Birthdays -- Juvenile fiction; Ducks -- Fiction; Domestic animals -- Fiction; Birthdays -- Fiction